Embodied Learning in Architecture: A Design Studio Model Utilizing Extended Reality - Jin Mi Lee (Buildings, 2025)
This study presents a novel pedagogical model for architectural education that integrates an extended-reality (XR) enhanced learning environment with embodied cognitive approaches. Addressing the limited application of technology-driven embodied experiences in architectural education and the lack of empirical studies assessing their effectiveness, this research examines how an XR-integrated design studio model facilitates ideation, design development, and reflective practice. Using an action-research methodology over 15 weeks, the study involved 12 third-year architecture students divided into experimental and control groups. The first two stages assessed the model’s impact on time management, decision-making, and students’ sense of ownership in the design process, while the third and fourth stages evaluated the quality of design outcomes, creativity, presentation skills, and overall student satisfaction. The findings demonstrate that an embodied cognition-based XR learning environment significantly enhances students’ experiential understanding of design proposals, encourages active exploration of design alternatives, and supports problem-solving within the architectural design process. The model also improved decision-making and time management by enabling students to comprehensively experience and evaluate their proposals. This study highlights the pedagogical value of integrating embodied cognition principles with immersive digital environments in architectural education and provides a structured framework for leveraging emerging technologies to enhance creativity and innovation in design studios.